Recipes for How to Force Oceanic Model Dynamics. (29th January 2020) - Renault, Lionel; Masson, S.; Arsouze, T.; Madec, Gurvan; McWilliams, James C.
Abstract: The current feedback to the atmosphere (CFB) contributes to the oceanic circulation by damping eddies. In an ocean‐atmosphere coupled model, CFB can be correctly accounted for by using the wind relative to the oceanic current. However, its implementation in a forced oceanic model is less straightforward as CFB also enhances the 10‐m wind. Wind products based on observations have seen real currents that will not necessarily correspond to model currents, whereas meteorological reanalyses often neglect surface currents or use surface currents that, again, will differ from the surface currents of the forced oceanic simulation. In this study, we use a set of quasi‐global oceanic simulations, coupled or not with the atmosphere, to (i) quantify the error associated with the different existing strategies of forcing an oceanic model, (ii) test different parameterizations of the CFB, and (iii) propose the best strategy to account for CFB in forced oceanic simulation. We show that scatterometer wind or stress are not suitable to properly represent the CFB in forced oceanic simulation. We furthermore demonstrate that a parameterization of CFB based on a wind‐predicted coupling coefficient between the surface current and the stress allows us to reproduce the main characteristics of a coupled simulation. Such a parameterization can be used with any forcing set, including future coupled reanalyses, assuming that the associated oceanic surface currents are known. A further assessment of the thermal feedback of the surface wind in response to oceanic surface temperature gradients shows a weak forcing effect on oceanic currents. Key Points: The Current FeedBack to the Atmosphere (CFB) can be parameterized in a forced oceanic model A parameterization of the CFB based on a predicted coupling coefficient is the best parameterization Scatterometers are not suitable to correctly represent the CFB in a forced oceanic model (unless coherent surface currents are known)